Agricultural R&D investments and policy development goals in Sub-Saharan Africa: Assessing prioritization of value chains in Senegal - Benfica, Rui (International Food Policy Research Institute, 2022)
This paper looks at the prioritization of agricultural value chains (VCs) for the allocation of R&D resources that maximize development outcomes (poverty, growth, jobs, and diets). Considering that growth in VCs affects those various outcomes differently, as expansion pathways result in the diverse use of production factors and inputs, trade-offs from linkages across sectors, and changes throughout the agri-food system, this analysis uses (i) the RIAPA dynamic computable general equilibrium model to identify which agricultural VCs, when expanded through TFP growth, provide the strongest effects on the development outcomes of interest; (ii) the perpetual inventory model (PIM) to represent the lagged effect of research through knowledge stocks of agricultural R&D investments; and (iii) information on the elasticities of VC agricultural activity TFP with respect to agricultural R&D knowledge stocks, to discuss the VC priority allocations of R&D resources in Senegal. Results indicate that no one VC (crop- or livestock-related) is the most effective at improving all development outcomes. When accounting for policy preferences that attribute relative priority weight to development objectives, results (based on a ranking scale) indicate that R&D investments for maximizing development objectives can be most effective in Senegal’s VCs for traditional export crops (growth, diets, jobs, and to some extent poverty), groundnuts (poverty, diets, and jobs), rice (poverty and jobs), poultry/eggs (diets and jobs), sorghum/millet (poverty and growth), and cattle (diets and growth). Other promising VCs with potential effects at scale if strategically targeted include vegetables (poverty, diets, and jobs), oilseeds (poverty and growth), and fruits (diets and jobs). While these results can inform strategies aimed at improving multiple development outcomes, future modeling needs to focus on deepening the standardization and integration of R&D investments costs into the framework, disentangle the relevance of different types of R&D investments sources, and bring together other factors and complementary agrifood system investment dimensions relevant to sustainable and inclusive agricultural VC growth.